Polybutadiene rubber/exfoliated graphite nanocomposites: Impact of filler on the thermal, mechanical and permeability characteristics. Issue 3 (August 2019) - George, Soney C; Abraham, Jiji; Jose, Thomasukutty; Thomas, Riya; Jacob, Teresa; Nair, Sangetha; Sasikumar, Soumya
In this report, we demonstrate that both mechanical behaviour and thermal stability of polybutadiene rubber (PBR) nanocomposites could be improved by incorporating exfoliated graphite (EG) using melt mixing method. Incorporation of the filler EG in the polybutadiene (PBD) matrix is confirmed by infrared spectra and X-ray diffraction analysis. The structural characteristics, mechanical properties and thermal properties of these newly modified PBR nanocomposites were systematically analysed and studied. Thermal properties of the nanocomposites were studied using thermogravimetric analysis under nitrogen atmosphere. Thermogravimetric studies showed that PBR8 is having higher thermal stability than that of the PBR gum sample. Mechanical properties like tensile strength, Young's modulus, tear strength, hardness and compression set of the nanocomposites were studied. Mechanical properties are also high for the modified PBR nanocomposites with maximum filler content. The permeability of organic vapours such as dichloromethane (CH2 Cl2 ), chloroform (CHCl3 ) and carbon tetrachloride (CCl4 ) through PBR/EG nanocomposites was also studied. In vapour permeation studies, PBR4 exhibits the least permeability in CH2 Cl2, CHCl3 and CCl4 solvents. Polybutadiene rubber–natural graphite (PBR/NG) nanocomposites were also prepared for comparison.